Vicia faba overcomes drought stress by spraying with Xerophytic Anabasis setifera extract - Amin, Mohamed A.; Shahhat, Ismail M. A. M.; Ismail, Mohamed A.; Nowwar, Abdelatti I.; Elsheikh, Salma Yousif Sidahmed; El-khawaga, Hend A.; Abdelwahab, Abdelrahman T.; Abdelfattah, Marwa A.; Elsherbeny, Sally A.; Abdel-Mageed, Ahmad. M.; Abdein, Mohamed A.; Bedawy, Ismail M.A. (Edelweiss Applied Science and Technology, 2024)
Drought stress is a prevalent environmental factor significantly impacting the faba bean (Vicia faba L.) crop. Anabasis setifera, a plant extract (ASE), has been found to potentially regulate plant responses to drought stress for the first time. The study examined the effects of applying an exogenous ASE on the physiological, biochemical, and yield responses of faba bean plants under three soil water regimes: well-watered (8-day irrigation intervals), moderate drought stress (12-day irrigation intervals), and severe drought stress (16-day irrigation intervals). The HPLC analysis of ASE revealed that it contains major phenolic compounds such as rutin, chlorogenic acid, gallic acid, ferulic acid, and coumaric acid. The extract also contains catechin, quercetin, syringic acid, pyro catechol, and methyl gallate. The study found that faba bean plants showed enhanced drought resistance after treatment with ASE. This treatment improved growth parameters like shoot and root length, fresh and dry weight, leaf and flower number, and reduced the negative impacts of drought stress on chlorophyll levels and metabolic activities. The study indicates that plants treated with ASE, including catalase, peroxidase, and polyphenol oxidase, can significantly mitigate drought stress effects, improve yield trials, and enhance seed components, making it cost-effective and ecologically beneficial.